Electrospun polyimide nanofiber-coated polyimide nonwoven fabric for hot gas filtration. Issue 9 (December 2018) - Wang, Liang; Cui, Lingyan; Liu, Yongsheng; Riedel, Johanna; Qian, Xiaoming; Liu, Yong
In the present work, heat-endurable polyimide nanofibrous membrane-coated commercial polyimide nonwoven fabrics were prepared by electrospinning synthesized polyamic acid solution on polyimide mats followed by a thermal imidization process. Polyimide synthesized was confirmed by Fourier-transform infrared spectroscopy and thermogravimetric analysis tests. A higher viscosity of precursor solution resulted in a nanofibrous network coated on the nonwoven fabrics. The coated filter showed lower dimension of pores and greater portion of small pores. The proportion of pores less than 10 µm reached as high as 71.2%. PM2.5 removal efficiency was increased from 81.4 to 97.2%. However, the pressure drop of air flow over the filters did not show significant changes. It suggested a facile method to improve the filtration performance of commercial polyimide nonwoven fabric filters.